Correlation of GNSS Observation Data Quality Resulted from TEQC Checking and Coordinate’s Precision - Yulaikhah Yulaikhah; Subagyo Pramumijoyo; Nurrohmat Widjajanti (Universitas Gadjah Mada, 2018)
GPS Positioning provides good coordinate accuracy that is up to a millimeter. However, some error sources such as multipath, atmospheric conditions and obstruction can reduce the quality of data and also coordinates. To minimize errors due to these factors, at the time of determining the station location, it is necessary to pay attention to the surrounding conditions, namely by looking for open areas and avoiding objects that can reflect GNSS signals. However, it is often not easy to find the ideal observation station location, which forms a good chain while being free from obstruction and multipath. Therefore, it is often necessary to prioritize certain factors over other factors. Information about the correlation between multipath, ionospheric conditions and the recording level of observational data on coordinate accuracy can be used as consideration in determining the location of control points for deformation monitoring and determining which factors are prioritized. This study aims to evaluate the correlation between data quality and coordinates precision.The used observation data are Sermo Reservoir control network and nine CORS BIG stations. The component data analyzed are multipath (MP1, MP2), ionospheric effects (IOD slips and IOD or MP slips) and the data recording level (obs). These components were resulted by checking with TEQC software, while the precision of the coordinates was obtained by processing with GAMIT / GLOBK software. Based on the correlation coefficient value, it is known that the recording level of observation data has the strongest correlation with a negative direction (ranging from -0.7 to -0.9). It is the ratio between the number of real observations to the number of possible ones. One factor that influences it is the obstruction in the field. In other words, in determining the location of GNSS observation stations, the conditions of obstruction in the vicinity need to be considered and prioritized.